Violence Against Infants and Children - Practical Implications Regarding Prevention Issues - Giacomuzzi, Salvatore; Garber, Klaus; Ertl, Marcus; Barinova, Natalia; Kocharian, Alexander (Psychological Counseling and Psychotherapy, 2020)
The article presents an overview of the problems of child violence, a wide range of its variants-physical, sexual and psychological violence, etc. It is shown that child violence has the quality of transgeneration, in one form or another, is reproduced in the next generations. The experience of violence is also a negative predictor of violent behavior that will manifest itself in the upbringing of their own children. Indicators of the epidemiology of violence are presented. The data vary greatly, for example, the prevalence of sexual violence ranges from 3% to 36%. Sexual violence mainly affects children between the ages of 6 and 13. Children under the age of 4 are most likely to suffer from physical and psychological abuse. Up to a third of victims of sexual violence may show appropriate behavior towards their own or other children. An overview of the factors that predispose / retard the formation of child violence is presented. These are factors such as age, gender, ethnic origin, disability, and social status of the parents. Prevention work should be based on a multi-level concept (multiple participants or institutions are involved). Appropriate measures to prevent violence should not (cannot) only target children / young people, but should also affect, in particular, parents and schools.